Ramdandi putra Rancang Bangun Alat Pemberian Pupuk, Keamanan Lahan Dan Penyortiran Tomat Berbasis Arduino Mega 2560 - Ramdandi; Emil Naf'an; Yogi Wiyandra (Journal of Computer Scine and Information Technology, 2023)
Utilizing modern technology in the field of tomato farming can increase production yields and simplify the production process. Currently, the process of selecting tomatoes in agriculture is still done manually, taking up time and being less accurate. Land security in plantations is also an important factor in determining the production outcome. Therefore, the use of modern technology is needed to ensure regular and scheduled fertilizer distribution, improve the accuracy of the tomato selection process, and ensure the security of the plantation land by adding cameras and warning alarms. To address various problems in the tomato farming production process, the use of advanced technology is needed. The use of computer technology in agriculture can help farmers in monitoring the condition of the plants, planning and scheduling fertilizer distribution, and optimizing the tomato selection process based on size. With the technology, tomato farming production can run efficiently, increasing tomato farming yields and improving the quality of the tomatoes produced. The security of the plantation land will also be maintained with the addition of additional security systems such as cameras and alarms